TRAINING EFFECTIVENESSS IN CONTINUING PROFESSIONAL DEVELOPMENT PROGRAM FOR GENERAL INSURANCE AGENTS (Journal of Technology and Operations Management, 2016)
Attaining training effectiveness for Continuing Professional Development (CPD) program will be beneficial for General Insurance Agents in performing their daily activities. The CPD Program for General Insurance Agents applies to all the practitioners in the general insurance agency force with effect from 1st January 2005 where the training hours and related requirements stipulated in the guidelines must be complied with. The Financial Mediation Bureau (FMB), now known as Ombudsman for Financial Services (OFS), a unit under the Central Bank of Malaysia had recorded 609 in 2015, 660 in 2014 and 742 in 2013 for General Insurance products. This report shows that the person who introduces to the public insurance products are not well versed with the product thus the knowledge imparted were different from what is it all about. In the insurance industry, the person is widely known as agent who plays the role as link between insurance companies and customers. This research has been conducted in two training session to find the best way to improve agent basic understanding on Negotiation thus connection to the higher-level knowledge is possible. Collaborative learning, which was introduced as a sharing session, through small group discussion has been chosen for the purpose of developing effective in undergoing the program. The Study concludes that agents are more comfortable to be open-minded and less stressful while learning with their peers compares to instructors. Based on interviews and observations, results found that collaborative learning do improve understanding and built critical thinking. The approach developed had resulted a more relax and conducive learning environment and the training effectiveness achieved served as evidence in agents’ performance